2003
DOI: 10.1103/physrevc.67.015803
|View full text |Cite
|
Sign up to set email alerts
|

Level densities for20<~A<~110

Abstract: A recent study of nuclear level densities for 20рAр70 found evidence that the level densities for nuclei off the stability line were lower than those for nearby nuclei on the stability line. This analysis has been extended to cover the mass range 20рAр110 with results that support the original conclusions. As part of the study, the variations with energy and mass number of the parity ratio and spin cutoff parameter are examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(94 citation statements)
references
References 8 publications
4
89
1
Order By: Relevance
“…The empty circles (red color) present the low energy fit, around 1-5 MeV, while the filled circles (black color) present the standard 5-25 MeV energy range fit. We can see that at low energies the fitted level density parameter a is slightly larger, but still it is not large enough to be compared with the empirical estimates [52,53]. …”
Section: Thermodynamic Description and Comparison With Phenomenolmentioning
confidence: 97%
See 2 more Smart Citations
“…The empty circles (red color) present the low energy fit, around 1-5 MeV, while the filled circles (black color) present the standard 5-25 MeV energy range fit. We can see that at low energies the fitted level density parameter a is slightly larger, but still it is not large enough to be compared with the empirical estimates [52,53]. …”
Section: Thermodynamic Description and Comparison With Phenomenolmentioning
confidence: 97%
“…This is the known Rosenzweig effect [54] described by Ericson [17] as due to "a considerably larger number of rearrangement possibilities when the shell is half-filled". The empirical estimates for the same nuclei are available from the level density at the neutron resonances energy [52], which do not show considerable shell effects, and by extrapolation from low-lying levels [53] where one can see very weak shell effects in the region of the mass number around A ≈ 50. The Constant in Eq.…”
Section: Thermodynamic Description and Comparison With Phenomenolmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the parity dependence at low excitation energies remains in question -the available level scheme [21] shows significant parity asymmetry below about 2.5 MeV. We attempted to check the results using a NLD with no asymmetry above 2.5 MeV, as well as for an asymmetry given by the dependence proposed in [27]. The same parameters of the parity dependence function as used in the analysis of MSC spectra of 96 Mo were adopted -∆ π = 3.2 MeV and C π = 1.0 MeV -see Ref.…”
Section: B Nuclear Level Density Modelsmentioning
confidence: 99%
“…According to this, the level density is expected to decrease with increasing |T 3 |. Recently, the analysis of the level density data [7] for nuclei with 20 ≤ A ≤ 110 [8], [9] has been carried out comparing different isospin dependences. It has been shown that, compared to the prescription based on the N-Z dependence, a reduction factor of the level density based on the distance from the valley of stability Z-Zo, where Zo is the atomic number of the beta stable isotope with the same mass, provides a better description of data.…”
Section: Introductionmentioning
confidence: 99%